Depletion of Neutrophils Exacerbates the Early Inflammatory Immune Response in Lungs of Mice Infected with Paracoccidioides brasiliensis - Paula Andrea Pino-Tamayo; Juan David Puerta-Arias; Damaris Lopera; Martha Eugenia Urán-Jiménez; Ángel González (Mediators of Inflammation)
Neutrophils predominate during the acute phase of the Paracoccidioides brasiliensis infection. Herein, we determined the role of the neutrophil during the early stages of experimental pulmonary paracoccidioidomycosis using a monoclonal antibody (mAb) specific for neutrophils. Male BALB/c mice were inoculated intranasally with 1.5×106 or 2×106 P. brasiliensis yeast cells. The mAb was administered 24 h before infection, followed by doses every 48 h until mice were sacrificed. Survival time was evaluated and mice were sacrificed at 48 h and 96 h after inoculation to assess cellularity, fungal load, cytokine/chemokine levels, and histopathological analysis. Neutrophils from mAb-treated mice were efficiently depleted (99.04%). Eighty percent of the mice treated with the mAb and infected with 1.5×106 yeast cells died during the first two weeks after infection. When mice were treated and infected with 2×106 yeast cells, 100% of them succumbed by the first week after infection. During the acute inflammatory response significant increases in numbers of eosinophils, fungal load and levels of proinflammatory cytokines/chemokines were observed in the mAb-treated mice. We also confirmed that neutrophils are an important source of IFN-γ and IL-17. These results indicate that neutrophils are essential for protection as well as being important for regulating the early inflammatory immune response in experimental pulmonary paracoccidioidomycosis.